2014
DOI: 10.1002/jsfa.6601
|View full text |Cite
|
Sign up to set email alerts
|

Quality determination of wheat: genetic determination, biochemical markers, seed storage proteins – bread and durum wheat germplasm

Abstract: The Hellenic cultivar Acheron is a good example since, despite the presence of the translocation, it also has very good bread-making quality and high yielding ability. It must be also mentioned that most of the Hellenic durum germplasm carries the gene locus Gli-B1 component, similar to γ45, which can be considered as an index of good end-product quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 94 publications
0
12
0
1
Order By: Relevance
“…Glutenins consist of different subunits of high molecular weight (HMW‐GS, 80–140 kDa) and low molecular weight (LMW‐GS, 31–51 kDa), which form large aggregates joined by disulfide bonds. Gluten properties determine dough strength, which is greater when there are higher proportions of HMW‐GS than LMW‐GS polymers, although a high glutenin/gliadin ratio is also important in determining the functional proprieties of the gluten …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutenins consist of different subunits of high molecular weight (HMW‐GS, 80–140 kDa) and low molecular weight (LMW‐GS, 31–51 kDa), which form large aggregates joined by disulfide bonds. Gluten properties determine dough strength, which is greater when there are higher proportions of HMW‐GS than LMW‐GS polymers, although a high glutenin/gliadin ratio is also important in determining the functional proprieties of the gluten …”
Section: Introductionmentioning
confidence: 99%
“…Gluten properties determine dough strength, which is greater when there are higher proportions of HMW-GS than LMW-GS polymers, although a high glutenin/gliadin ratio is also important in determining the functional proprieties of the gluten. 3 Environmental factors and agronomic management play an important role in determining wheat quality characteristics. For example, temperature and precipitation during grain filling and nitrogen (N) availability are key factors in seed protein accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Quality is an important determinant in wheat breeding since the environment usually less affects its genetic background and sufficiently influences the commercial value of a cultivar (Varzakas et al, 2014). Wheat quality depends on the presence of certain alleles at loci, which are responsible for end product quality.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat quality depends on the presence of certain alleles at loci, which are responsible for end product quality. Thus, if a certain cultivar possesses some specific allele combination at crucial loci, then it appears quite possible to exhibit valuable qualitative traits in terms of end product quality (Varzakas et al, 2014). However, production of a cultivar conferring improved quality also require a growing environment that favors expression of this genetic potential in order, for this, to lead to the eventual production of high-quality grain (Yong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the wide use of the 1BL.1RS translocation, and it is suggested that new sources of resistant genes must be obtained (Tang et al 2008). The presence of the 1BL.1RS wheat rye translocation can be detected with biochemical and molecular markers (Xynias et al 2007;Varzakas et al 2014). Seed storage proteins are the most common biochemical marker in wheat and an extended review on their application in wheat breeding was published by Xynias et al (2007).…”
Section: Introductionmentioning
confidence: 99%